Transformation of structures and reconfiguration of professional roles: when principals and teaching teams in two cycles of orientation in a Swiss canton face up to the challenges of inclusive education - Noël, Isabelle (Avances en Supervisión Educativa, 2024)
This article is the third in a series devoted to the role of school principals in the development of inclusive education in schools (Noël, 2022; Noël & Rody, 2024). Based on data collected in the context of action research carried out in two orientation cycles in a Swiss canton, it reports on the main issues and challenges faced by school principals and, more broadly, by teaching teams in setting up more inclusive structures and practices. Various obstacles, but also the levers and resources activated to this end in these two contexts, are identified, analysed and discussed. Mobilising the different professionals in order to intensify and optimise collective work on the one hand, but also to change professional roles and practices on the other, seems to be a key challenge for school leaders. On the basis of the results presented, a number of avenues are suggested for instilling and supporting the development of an inclusive dynamic in schools.
Keywords: educational institution; inclusive education; inclusive dynamic; role of school leadership; collective work; interprofessional partnership